2006
DOI: 10.1073/pnas.0609025103
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-like 4 prevents metastasis through inhibition of vascular permeability and tumor cell motility and invasiveness

Abstract: Angiopoietin-like 4 (ANGPTL4), a secreted protein of the angiopoietin-like family, is induced by hypoxia in both tumor and endothelial cells as well as in hypoxic perinecrotic areas of numerous cancers. Here, we investigated whether ANGPTL4 might affect tumor growth as well as metastasis. Metastatic 3LL cells were therefore xenografted into control mice and mice in which ANGPTL4 was expressed by using in vivo DNA electrotransfer. Whereas primary tumors grew at a similar rate in both groups, 3LL cells metastasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
221
6
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(234 citation statements)
references
References 25 publications
6
221
6
1
Order By: Relevance
“…Notably, angiopoietin-like 4, a matricellular protein endowing breast tumours with the capacity to disrupt lung capillaries and seed pulmonary metastases 35,38 , was absent from our proteomic analysis. In line with this, angiopoietin-like 4 was reported to prevent metastasis of melanoma B16 cells by inhibiting vascular permeability and tumour cell motility 39 .…”
Section: Discussionmentioning
confidence: 74%
“…Notably, angiopoietin-like 4, a matricellular protein endowing breast tumours with the capacity to disrupt lung capillaries and seed pulmonary metastases 35,38 , was absent from our proteomic analysis. In line with this, angiopoietin-like 4 was reported to prevent metastasis of melanoma B16 cells by inhibiting vascular permeability and tumour cell motility 39 .…”
Section: Discussionmentioning
confidence: 74%
“…ANGPTL4 (or specific domains of the protein) has been shown to regulate endothelial cell adhesion (24) and to promote angiogenesis under some circumstances (21,22,35), but also to inhibit angiogenesis in other circumstances (23)(24)(25)(26). More recently, several studies have suggested similarly discordant functions for this factor in tumor dissemination: whereas systemic ANGPTL4 secretion in mice inhibited melanoma metastasis through inhibition of vascular permeability and tumor cell invasiveness (29), TGFβ-mediated induction of ANGPTL4 by breast cancer cells primed these cells for lung metastasis by increasing the permeability of lung capillaries (28).…”
Section: Discussionmentioning
confidence: 98%
“…Collectively, these findings suggest that ANGPTL4 is comparable to VEGF in its contribution to the promotion of angiogenic phenotype by vGPCR. Emerging evidence suggests that ANGPTL4 may play a role in vessel permeability (28,29). This prompted us to assess the relative contribution of this factor to the exudative phenotype of KS lesions.…”
Section: Vegf Is Not Sufficient For the Exudative Phenotype In Vgpcr mentioning
confidence: 99%
“…Angiopoietin-like 4, structurally similar to the angiopoietins, protects vascular integrity in contexts of myocardial infarction and tumor metastasis; Angptl4-KO mice showed altered VEGFR2/VE-cadherin complexes and disrupted endothelial cell adherens junctions (32,33). Cysteine-rich angiogenic inducer 61 (encoding by Cr61), produced by fibroblasts and endothelial cells, is considered an important matrix protein promoting tissue repair and immune cell adhesion by binding various integrins; high expression of this molecule inhibits transmigration of innate and adaptive immune cells (34).…”
Section: Discussionmentioning
confidence: 99%